Islamic Education in Indonesia: Study of Azyumardi Azra's Thought - M. Adib Fuadi Nuriz; Jaffary Awang (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2018)
Globalization lately has an impact on Islamic education of Muslim society. In Indonesia, the Islamic education currently has a great contribution to national development. But it is not easy to achieve the purpose of Islamic education because of a problem with the concept and method of Islamic education itself. This research examines the current Islamic education thought, according to Azyumardi Azra. This is a literature study using content analysis and critical approach. As the results and conclusion, I found that Azyumardi Azra’s thought that Moslem people can answer the modernity only by become of Islamic education that Muslims people should answer the modernity by modern education, with integrating between the classical model of Islamic education and modern western education, building the Islamic education more inclusive, liberal, and democratic. Some critics for this, the modernization in Islamic education developed by Azyumardi Azra was influenced by the western thought especially the view of pluralism and liberalization where this view need to criticised within Islamic worldview.